Analyzing Weekly Productivity Dynamics in Steel Fabrication Services Using the Objective Matrix (OMAX) Method Integrated with Root Cause Analysis (Case Study: PT SWA) - Alfadito Noval Prasetya; Elly Ismiyah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
PT SWA is a steel fabrication service company operating in the construction sector, where productivity performance plays a critical role in meeting project schedules and cost targets. This study aims to measure weekly productivity levels in the steel fabrication process and to identify the dominant factors contributing to productivity fluctuations. The research employs the Objective Matrix (OMAX) method to quantify productivity performance using selected productivity ratios, which is then integrated with Root Cause Analysis (RCA) to identify the underlying causes of productivity decline. The results reveal significant weekly productivity dynamics during the ten-week observation period. Productivity increased during Weeks 1 and 2, with the highest improvement recorded in Week 2, achieving a productivity index of 190%. However, a continuous decline was observed from Weeks 3 to 10, with the lowest productivity index occurring in Week 8 at −78.33%. The analysis indicates that machine-related disruptions, substandard raw materials, and insufficient operator skills were the primary contributors to low-performing productivity ratios and overall productivity deterioration. The novelty of this study lies in integrating weekly OMAX-based productivity measurement with RCA to provide data-driven, actionable improvement insights within the context of steel fabrication services. The findings offer practical managerial implications, highlighting the importance of preventive maintenance planning, material quality control, and operator competency development to stabilize and improve productivity performance. Keywords: Productivity Measurement, Objective Matrix (OMAX), Root Cause Analysis, Steel Fabrication Services